Progress of research on Traditional Chinese Medicine five-element music therapy in clinical nursing of patients with cancer (中医五行音乐疗法在肿瘤患者临床护理中的研究进展) - HAN Qiuhong (韩秋红); MA Yun (马芸); XU Zhe (许哲) (中西医结合护理)
This paper reviewed studies on application of Traditional Chinese Medicine five-element music therapy in in clinical nursing of patients with cancer from perspectives of cancer-related anxiety, depression, insomnia and other adverse reactions. The meaning of TCM five-element and five-tone, TCM theory and mechanism were briefly discussed to provide reference for establishment of archives of five-element music and promotion of TCM five-element therapy. (本文分析了五行音乐在肿瘤患者中的应用, 主要从五行音乐疗法对肿瘤患者相关焦虑抑郁情绪、失眠等方面的治疗进行阐述, 简单介绍了中医“五行”、“五音”的含义、中医理论、作用机制, 旨在通过数据分析建立和推广相对完善的五行音乐库, 进一步推广中医五行音疗法。)